Primary carcinoma of the fallopian tubes: a case report - Mulmule, Lalita Rajiva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Primary fallopian tube carcinoma (PFTC) is considered a rare and aggressive type of tumour, representing 0.14-1.8% of the total gynaecological malignancies. About 1200 cases in all have been reported till now. It is very important to diagnose these neoplasms at an early stage as the survival rates drop dramatically with advanced stages. However, a correct diagnosis is rarely achieved preoperatively and PFTC is often mistaken for ovarian malignancies, pelvic inflammatory disease, pelvic peritonitis. We are reporting the case of a 53 year old female who presented with abnormal vaginal bleeding and discharge, and was diagnosed to have PFTC, papillary type FIGO II, only on histopathology after undergoing total abdominal hysterectomy with bilateral salphingo oophorectomy.